Magnetic Resonance Imaging Volumetry of Facial Muscles in a Face Transplant Recipient - Rami S. Kantar, MD, MPH; Nicole Wake, PhD; Allyson R. Alfonso, BS, BA; William J. Rifkin, MD; Elie P. Ramly, MD; J. Rodrigo Diaz-Siso, MD; Eduardo D. Rodriguez, MD, DDS (Plastic and Reconstructive Surgery, Global Open, 2019)
Summary:. Face transplantation has evolved into a viable reconstructive option for patients with extensive facial disfigurement. Because the first face transplant procedure was described in 2005, the safety and feasibility of the procedure have been validated, and the focus of the field has shifted toward refining functional and esthetic outcomes. Recovery of muscle function following facial transplantation is critical to achieving optimal facial function and restoring facial expression. Assessment of facial muscle function in face transplant recipients has traditionally relied on clinical evaluation. In this study, we describe longitudinal changes in facial muscle volumes captured through quantitative magnetic resonance imaging in a face transplant recipient and compare these findings with functional outcomes evaluated through clinical assessment.